Antioxidant Activity of Carotene-rich Sweet potato Extracted with an Hexane-Ethanol Solvent mixture - Nareswari, Nadia; Estiasih, Teti; Murtini, Erni Sofia (Jurnal Teknologi Pertanian, 2006)
A study was conducted to assess the antioxidant activity of carotene-rich sweet potato extracted with various ratios of solvent mixture hexane and ethanol. The respective ratios of solvent mixture hexane to ethanol were 4:0, 3:1, 2:2, 1:3 and 0:4. Observations were made on the colour parameter value, beta carotene, phenol content and antioxidant activity i.e radical scavenging and peroxide inhibition activities. The radical scavenging activity of the extract varied with the ratio of the solvent found at the hecane to ethanol ratio of 1:3 (89.744%), followed by the ration of 2:2 (88.539%), 4:0 (87.305%), 3.1 (86.923%) and 0:4 (83.897%). Based on the value of EC50 and the ability to react with radicals, the extract of hexane to ethanol 1:3 and 0:4 were the two best in the radical scavenging activity, as shown by the correlation coefficient of 74.9%. Similarly, the peroxide formation inhibition activity also varied with the ration of the solvent i.e. 61.126% (2:2), followed by 53.035% (1:3), 50.127% (0:4), 43.561% (3:1) and 36.046% (4.0). It seems that the carotenoids were the most influenced factor to the peroxide formation inhibition activity, as shown by the correlation coefficient of 63.4%. Keywords: Carotene-rich sweet potato, ratio of hexane:ethanol, antioxidant activity